1998
DOI: 10.1159/000014333
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion with Polymyxin B- Immobilized Fiber Attenuates the Increased Plasma Levels of Thrombomodulin and von Willebrand Factor from Patients with Septic Shock

Abstract: Aims: The present study assessed whether plasma levels of thrombomodulin and von Willebrand factor (vWF) are altered in patients with septic shock and whether treatment with polymyxin B-immobilized fiber (PMX-F) affects these levels. Methods: Twenty-four patients with septic shock and 20 normal healthy controls were included in this study. Plasma levels of thrombomodulin and vWF were measured by enzyme immunoassay (EIA). The treatments with direct hemoperfusion using PMX-F column on patients with septic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Recently, Ebihara et al [27] clearly demonstrated that PMX-F significantly decreased blood endotoxin levels, associated with a remarkable improvement in survival rate. Moreover, that group provided scientific evidence that treatment with PMX-F attenuates the increased plasma levels of thrombomodulin and von Willebrand factor in patients with septic shock [28]. Recently, Kodama et al [29] clearly demonstrated results similar to our present data.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Ebihara et al [27] clearly demonstrated that PMX-F significantly decreased blood endotoxin levels, associated with a remarkable improvement in survival rate. Moreover, that group provided scientific evidence that treatment with PMX-F attenuates the increased plasma levels of thrombomodulin and von Willebrand factor in patients with septic shock [28]. Recently, Kodama et al [29] clearly demonstrated results similar to our present data.…”
Section: Discussionsupporting
confidence: 90%
“…On the basis of previous studies, we reported that PMX-F treatment is effective in reducing myocardial damage, systemic permeability, endothelial cell damage, and platelet damage in patients with sepsis [5,6,16,17]. In the present study, amino acid imbalance was ameliorated by PMX-F treatment due, in part, to a reduction of the plasma endotoxin levels.…”
Section: Discussionsupporting
confidence: 65%
“…In septic shock, some investigators have reported increased levels of E-selectin and adhesion molecules in both plasma and in the supernatant of cultured vascular endothelial cells [17,18]. We have shown previously that plasma levels of von Willebrand factor and thrombomodulin, which are thought to be indicators of endothelial cell injury, were significantly increased in patients with septic shock [19]. In addition, we have shown that plasma MMP-9 concentrations and monocyte MMP-9 mRNA levels may be useful prognostic markers in septic shock [8].…”
Section: Discussionmentioning
confidence: 78%